Acute fatty liver of pregnancy: An atypical case report - Subono, Riska; Hikmah, Nurul (Majalah Obstetri & Ginekologi, 2024)
HIGHLIGHTS Acute Fatty Liver of Pregnancy (AFLP) is an uncommon condition but life-threatening obstetric emergency, that increases the risk of fetal death due to preterm birth. AFLP can be challenging for primary health workers (especially for general practitioners [GP] and midwives) since it mimics preeclampsia, viral hepatitis, intrahepatic cholestasis of pregnancy, and HELLPS syndrome, so more concern is needed in this case.   ABSTRACT Objective: To present an atypical case of acute fatty liver of pregnancy. Case Report: A 33-year-old woman was referred to the Emergency department of Dr. Soedarso Tertiary Referral Hospital, Pontianak, Indonesia, previously from the district hospital located over 580 km with diagnosis of multigravida (gravida 3 para 2) at 31 weeks gestation, suspected acute fatty liver disease (AFLP), severe oligohydramnios, and intrauterine growth restriction (IUGR). The patient had a history of nausea, vomiting, epigastric pain, polydipsia and polyuria, and seizure for less than 5 minutes with loss of consciousness. The patient originally did not know she was pregnant and using a contraceptive implant. She missed her period in the last six months ago, which was the first onset of epigastric pain. Further clinical examination resulted in pitting oedema but jaundice as a cardinal sign was not present. Laboratory data showed leukocytosis, normal haemoglobin level, normal blood glucose, hyperuricemia, increased function liver test with high transaminase and bilirubin, normal coagulation profile. Urinalysis showed proteinuria. The viral hepatitis and HIV tests were negative. Transabdominal ultrasound demonstrated a single intrauterine pregnancy with no echogenic liver features. Cardiotocography (CTG) showed category 2. This patient was diagnosed with AFLP based on Swansea Criteria (7 out of 10) and terminated pregnancy two days after diagnosis. A baby boy was born with birth weight 1.100 gr, birth length 34 cm, apgar score (AS) 9 and 10 at 1 and 5 minutes. The mother had a good prognosis, while the baby died on day 23 of life. Conclusion: Acute fatty liver during pregnancy is an uncommon but life-threatening obstetric emergency. Early screening, diagnosis, timely handling delivery, and intensive supportive care are essential to decrease morbidity and mortality for both mother and fetus. Multidisciplinary opinion needed for the best management of this case.